Assessment of farmers perception on socio-economic status after NABARD refinance – An empirical study with reference to select districts of Andhra Pradesh - Boddu, Kalpana; Ram, B. Mohan Venkata (Edelweiss Applied Science and Technology, 2025)
Agriculture is the backbone of India's economy, ensuring food security, employment, and overall economic development. It supports the livelihoods of a significant portion of the population and is vital to India's socio-economic structure. Recognising its importance, the Government of India has implemented various initiatives and significantly increased budget allocations to strengthen this essential sector. Agriculture serves as the primary source of employment in rural areas, engaging a substantial portion of the rural workforce. According to the Food and Agriculture Organization (FAO), over 55% of the population in many developing countries is employed in the agricultural sector. This industry not only provides jobs for farmers but also for individuals involved in various stages of the agricultural value chain, including processing, transportation, and retail. The objective of the study is to gauge the perceptions of farmers towards their socio-economic status after NABARD refinance. Responses from beneficiaries were gathered, coded, and entered into SPSS 25 for tabulation. The collected data underwent analysis using multiple reliable and validated tools and procedures. Advanced statistical tools such as Chi-square, t-test, and Analysis of Variance (ANOVA) were utilized. Simple descriptive statistics were employed to summarize the characteristics of respondents and the frequency of NABARD beneficiaries. The current study expects to find a strong interrelation between RRBS and NBFCS/MFIS, while other agencies show independent or negligible correlations, reflecting NABARD’s varied refinancing strategies.